Randomized controlled phase I trial for a novel peripheral parenteral nutrition formula containing dextrose, amino acids, fat emulsion, electrolytes, and FDA2000 recommendation-based vitamins. (August 2022) - Fukatsu, Kazuhiko; Shineha, Ryuzaburo; Katayose, Satoshi; Kawauchi, Yoshiyuki; Nakayama, Mitsuo
Summary: Background & aims: We developed the world's first all-in-one type peripheral parenteral nutrition product containing dextrose, amino acids, fat emulsion, electrolytes and vitamins, according to the FDA 2000 recommendation. This phase I trial examined the safety and changes in nutritional parameters in healthy participants. Methods: A single-center, randomized, open-label, active-controlled trial was performed in single ascending dose (SAD: Step 1–3) and multiple dose (Step 4) studies. Participants were administered a single dose of OPF-105 (test solution: 150 g of dextrose, 60 g of amino acids, 40 g of fat, 1240 kcal of total energy per 2200 mL, and 106 NPC/N ratio, with multivitamins, n = 17) or BFI (control solution: 150 g of dextrose, 60 g of amino acids, 840 kcal of total energy per 2000 mL, and 64 NPC/N ratio, with vitamin B1, n = 18) with three ascending doses (Step 1: 550 mL, Step 2: 1100 mL, and Step 3: 2200 mL) in the SAD study, or received multiple doses with Step 3 amount of OPF-105 (n = 5) or BFI (n = 6) for 3 days (Step 4) via peripherally inserted venous catheters. The safety and nutritional parameters were assessed. Results: There were no serious adverse events or events requiring discontinuation of the solution administration in either group. Blood urea nitrogen (BUN) levels remained within the normal range in both groups (Step 1–4). However, they gradually increased during the time course of the study in the BFI group but not in the OPF group (Step 4), suggesting the prevention of body protein breakdown. Blood triglyceride (TG) levels increased after administration in the OPF group but promptly returned to the pre-administration level (Step 1–4). Blood total ketone body levels increased the day after administration in both groups, which may imply a lower degree of starvation (Step 1–3), but the increase in the OPF group was milder than that in the BFI group (Step 4). Blood vitamin B6 and folic acid levels were maintained within the normal ranges in the OPF group but were near the lower limit in the BFI group (Step 1–4). Blood vitamin C levels showed almost lower limit in the two groups (Step 1–3), but increased only in the OPF group (Step 4). Blood vitamin K levels in the BFI group remained near the lower limit of the normal range, but those in the OPF group were higher than the upper limit at the end of administration and quickly returned to the pre-administration level (Step 1–4). Conclusions: This trial suggests that the newly developed formula (OPF-105) improves fat metabolism, maintains vitamin profiles, and may prevent body protein and fat breakdown and can be safely administered to healthy participants. Registration number of Clinical Trial: UMIN000046915; https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000053479 .